2008
DOI: 10.1007/s11434-008-0095-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of RNA silencing encoded by Rice gall dwarf virus genome segment 11

Abstract: Rice gall dwarf virus (RGDV) is an important rice pathogen in China andSoutheast Asia. However, little is known about the molecular mechanisms of RGDV interactions with plant cells. Here, we have identified an RGDV protein, Pns11, which acts as a suppressor of RNA silencing in coinfiltration assays with the reporter, green fluorescent protein (GFP) in transgenic Nicotiana benthamiana line 16c carrying GFP. Pns11 suppressed local and systemic silencing induced by sense RNA. The spread of mobile RNA silencing si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…To date, the function of the protein encoded by S12 and Pns12 remains unknown. A previous report showed that RGDV S11 encodes a silencing suppressor [21]. In this study, we present evidence that Pns12 of RGDV also has silencing suppressor activities.…”
Section: Rice Gall Dwarf Virus (Rgdv) Is a Member Of The Genussupporting
confidence: 66%
See 2 more Smart Citations
“…To date, the function of the protein encoded by S12 and Pns12 remains unknown. A previous report showed that RGDV S11 encodes a silencing suppressor [21]. In this study, we present evidence that Pns12 of RGDV also has silencing suppressor activities.…”
Section: Rice Gall Dwarf Virus (Rgdv) Is a Member Of The Genussupporting
confidence: 66%
“…In addition, Cui et al [47] demonstrated that a Geminivirus, Tobacco curly shoot virus Y35 (TbCSV-Y35), could process three VSRs, namely AC2, AC4, and βC1. Liu et al [21] have reported that RGDV Pns11 was a silencing suppressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most viruses can achieve self-assembly effectively in eukaryotic expression systems. For example, Orthoreovirus [10] , Rotavirus [22] and Bluetongue virus [9] in the Reoviridae family can assemble into single-, double-or triple- experiments, such as S1 fragment encoding RNAdependent RNA polymerases (RdRp) [13] , S5-encoded minor core protein having the guanylyltransferase activity [8] , and S11 encoding an RNA silencing suppressor [11] , etc. In the genus Phytoreovirus, the structure and assembly mechanism of RDV particles have been most clearly described.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rice-infecting reoviruses, Pns10 encoded by RDV segment 10 and Pns11 encoded by RGDV segment 11, have been shown to have RNA silencing suppressor activity (Cao et al, 2005; Zhang et al, 2005; Liu et al, 2008). …”
Section: Conferring Resistance Against Rice-infecting Reovirusesmentioning
confidence: 99%